2022
DOI: 10.1101/2022.04.22.489119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A phased chromosome-level genome and full mitochondrial sequence for the dikaryotic myrtle rust pathogen, Austropuccinia psidii

Abstract: The fungal plant pathogen Austropuccinia psidii is spreading globally and causing myrtle rust disease symptoms on plants in the family Myrtaceae. A. psidii is dikaryotic, with two nuclei that do not exchange genetic material during the dominant phase of its life-cycle. Phased and scaffolded genome resources for rust fungi are important for understanding heterozygosity, mechanisms of pathogenicity, pathogen population structure and for determining the likelihood of disease spread. We have assembled a chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…This overall chromosome synteny was consistent with the dominant synteny detected by comparing BUSCO genes (Henningsen et al 2022). In addition, this conservatism of chromosome synteny was also detected between species from different genera (Edwards et al 2022).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This overall chromosome synteny was consistent with the dominant synteny detected by comparing BUSCO genes (Henningsen et al 2022). In addition, this conservatism of chromosome synteny was also detected between species from different genera (Edwards et al 2022).…”
Section: Discussionmentioning
confidence: 72%
“…This overall chromosome synteny was consistent with the dominant synteny detected by comparing BUSCO genes (Henningsen et al 2022). In addition, Edwards et al (2022) reported that Austropuccinia psidii (Sphaerophragmiaceae, Pucciales), was in parallel with species in Pucciniaceae, Pucciales, indicating that conservatism of chromosomal synteny can exist at a family level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several distantly related rust fungi within the Pucciniamycotina subdivision are known to have 18 haploid chromosomes (Schwessinger et al . 2020; Wu et al 2021; Edwards et al . 2022), a much greater variation in chromosome number may be expected among the Pucciniales, particularly in ancient rusts.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Tavares et al (2013) determined between 7-13 chromosomes using both electrophoretic and cytological karyotyping, as well as fluorescence in-situ hybridization of two races of H. vastatrix (race II -isolate 1065 and race VI -isolate 71) from the CIFC/ISA collection. While several distantly related rust fungi within the Pucciniamycotina subdivision are known to have 18 haploid chromosomes (Schwessinger et al 2020;Wu et al 2021;Edwards et al 2022), a much greater variation in chromosome number may be expected among the Pucciniales, particularly in ancient rusts.…”
Section: Hv178a Chromosome Numbers Align With Cytological Studiesmentioning
confidence: 99%